(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper investigates a general subclass of analytic functions defined in the open unit disk involving a multiplier transformation. Employing the linear approximation theorem, we present sharp coefficient estimates, growth and distortion results, and radii for geometric properties such as close-to-convexity, starlikeness, and convexity. Our approach generalizes several known results.